2020
DOI: 10.1101/2020.01.10.902528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The novel reversible LSD1 inhibitor SP-2577 promotes anti-tumor immunity in SWItch/Sucrose-NonFermentable (SWI/SNF) complex mutated ovarian cancer

Abstract: Chromatin remodeling SWItch/Sucrose-NonFermentable (SWI/SNF) complexes, initially identified in yeast 20 years ago, are evolutionarily conserved multi-subunit protein complexes that use the energy from hydrolysis of adenosine triphosphate (ATP) to remodel nucleosome structure and modulate transcription. Mutations in proteins of SWI/SNF complexes occur in 20% of human cancers including ovarian cancer (OC). Approximately 50% of ovarian clear cell carcinoma (OCCC) carries mutations in the SWI/SNF subunit ARID1A w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…A large number of preclinical studies have revealed the critical role of epigenetic factors in antitumor immune responses and reversal of immunosuppression, particularly in PD-L1/PD-1 blockade (72,91,172,184). The rational application of a combination of multiple epigenetic targeted drugs, including DNMT inhibitors and histone-modifying enzyme inhibitors, with anti-PD-L1 immunotherapy, represents an opportunity to improve antitumor efficacy, enhance response rates to PD-1/PD-L1 blocking antibodies and reverse drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of preclinical studies have revealed the critical role of epigenetic factors in antitumor immune responses and reversal of immunosuppression, particularly in PD-L1/PD-1 blockade (72,91,172,184). The rational application of a combination of multiple epigenetic targeted drugs, including DNMT inhibitors and histone-modifying enzyme inhibitors, with anti-PD-L1 immunotherapy, represents an opportunity to improve antitumor efficacy, enhance response rates to PD-1/PD-L1 blocking antibodies and reverse drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine demethylase 4B (KDM4B) is a demethylase that acts on lysine, and its silencing can reduce PD-L1 expression by promoting H3K27me3 expression and reducing homeobox C4 (HOXC4) expression in colorectal cancer cells (90). In addition, lysine-specific histone demethylase 1 (LSD1) regulates the chromatin landscape and gene expression by demethylating proteins, such as histone H3 (91). HCI-2509, a noncompetitive highly potent reversible LSD1 inhibitor, upregulates PD-L1 expression in breast cancer cells in a dose-dependent manner (92).…”
Section: Regulation Of Pd-l1 Expression In Solid Tumors By Histone Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, LSD1 has proven to be highly expressed in SWI/SNF‐mutant cancers. Inhibition of LSD1 by SP‐2577 reduces the proliferation of SWI/SNF‐deficient ovarian cancer cell lines, suggesting SP‐2577 as a treatment for this cancer type [85].…”
Section: Targeting Epigenetic Erasers In Cancermentioning
confidence: 99%
“…SP-2577 is an LSD1 inhibitor. SP-2577 promoted ERV expression in ovarian cancer cells and activated the dsRNA-induced IFN pathway, which facilitated cytokine expression and infiltration of immune cells in ovarian hypercalcemic organoids (103). CX-5461, an RNA polymerase I inhibitor, led to the accumulation of cytoplasmic dsDNA activating the cGAS-STING-TBK1-IRF3 innate immune pathway, which induced IFN-I and promoted the secretion of IL-6 and CXCL10, contributing to T cell infiltration (104).…”
Section: Targeted Drug Therapymentioning
confidence: 99%